Are migrants discriminated against in Chinese urban labour markets? - Jason Gagnon; Theodora Xenogiani; Chunbing Xing (IZA Journal of Labor & Development, 2014)
We use a nationally representative survey to investigate the incidence of discrimination against internal migrant workers in urban China, considering both migrants from rural areas (rural migrants) and those from other urban areas (urban migrants). We find that both rural and urban migrants are discriminated out of jobs with formal labour contracts. Results also suggest that urban migrants are compensated for working in the informal sector by earning higher wages. There is evidence however of wage discrimination against rural hukou status. A semi-parametric method suggests a larger discrimination against migrants in the upper half of the wage distribution. Discrimination against migrants seems not to decrease as their duration of stay in the urban labour market increases.
Keywords: J7; J51; O15; N35; 330; China; Discrimination; Labour market; Wages; Internal migration